2022
DOI: 10.3390/antibiotics11121687
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Analysis of a Twitter-Disseminated Survey Reveals New Patient Perspectives on the Impact of Urinary Tract Infection

Abstract: Few studies have harnessed social media to explore patients’ experiences with urinary tract infection (UTI); therefore, we captured UTI experiences and future research suggestions through a Twitter-disseminated survey. The survey posed three qualitative questions inquiring about the impact of UTIs, greatest UTI management hurdle, and research suggestions. We also asked participants to rate how seriously others perceive UTIs and the importance of UTIs in their life (scale: 1–100 (highest)). The study period spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…14 Women identified UTIs with the word "bother," 15 with a Twitter-disseminated survey describing a drastic impact on physical and mental health leading to severe limitations in life activities. 16 Recurrent UTIs in people with n ORIGINAL RESEARCH spinal cord injuries demonstrated distress from perceptions of it as stigmatizing with fear of antibiotic reliance, seeking alternative prevention and management strategies, and causing barriers to social participation with adverse effects on quality of life. 17 In addition, women with at least 1 uncomplicated UTI expressed negative emotions with activities of daily life, relationships, treatment and management approaches, treatment failure, and recurrent uncomplicated UTIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Women identified UTIs with the word "bother," 15 with a Twitter-disseminated survey describing a drastic impact on physical and mental health leading to severe limitations in life activities. 16 Recurrent UTIs in people with n ORIGINAL RESEARCH spinal cord injuries demonstrated distress from perceptions of it as stigmatizing with fear of antibiotic reliance, seeking alternative prevention and management strategies, and causing barriers to social participation with adverse effects on quality of life. 17 In addition, women with at least 1 uncomplicated UTI expressed negative emotions with activities of daily life, relationships, treatment and management approaches, treatment failure, and recurrent uncomplicated UTIs.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse symptom descriptions were typical for women with cystitis, 12 with recurrent UTIs in older women affecting physical and psychological health, restricting daily life, increasing dependence on access to relief, and receiving inadequate care 13 with fears that their symptoms may indicate something more serious than a UTI 14 . Women identified UTIs with the word “bother,” 15 with a Twitter-disseminated survey describing a drastic impact on physical and mental health leading to severe limitations in life activities 16 . Recurrent UTIs in people with spinal cord injuries demonstrated distress from perceptions of it as stigmatizing with fear of antibiotic reliance, seeking alternative prevention and management strategies, and causing barriers to social participation with adverse effects on quality of life 17 .…”
Section: Discussionmentioning
confidence: 99%
“…6-9 Recurrent UTIs exert negative impacts on several aspects of physical, mental, and sexual health, with a subset of patients experiencing extreme symptoms. 11-14…”
mentioning
confidence: 99%
“…[6][7][8][9] Recurrent UTIs exert negative impacts on several aspects of physical, mental, and sexual health, with a subset of patients experiencing extreme symptoms. [11][12][13][14] As recurrent UTIs require repeated courses of antibiotics coupled with prophylactic treatment regimens, this increased exposure places patients at higher risk for developing antimicrobial resistance and treatment failure. 15 Indeed, a Brazilian study conducted among patients seen in the ED or urological office found those with recurrent cystitis or pyelonephritis had significantly higher resistance to 13 antibiotics compared to those with sporadic UTI.…”
mentioning
confidence: 99%
“…5 A recent twitter survey captured similar themes regarding UTIs in women, including the profound impact on physical and mental health, inadequate treatment and diagnosis, feelings of limited knowledge about pathophysiology, and gaps in research. 7 Due to these experiences and feelings of dissatisfaction, women often seek medical management and insights from alternative sources to medical providers, such as online forums, herbalists, and acupuncturists. 5 Approximately twothirds of women with rUTI wait until they have experienced four UTIs before beginning prophylactic measures.…”
mentioning
confidence: 99%